Lymphtaping® and breast cancer-related lymphoedema: an integrative review (Research, Society and Development, 2022)
Introduction: The lymphedema related to breast cancer (LRCM) is a chronic condition that can arise due to changes in structure and lymphatic function from the treatment of this neoplasm. The gold standard treatment of this sequel is complex physical therapy (CBT); however, there may be difficulty in adhering to this therapy due to factors such as temperature, application and aesthetics. In this context, Lymphotaping® is an alternative therapy. Objective: To evaluate the efficiency of Linfotaping® in the treatment of CRIM, analyzing its effects on quality of life, volume and functionality of the affected arms. Methodology: This is a literature review, with a systematic search in PubMed, Web of Science, Embase, Scopus, PEDro, SciELO and LILACS. The search terms were "Breast Cancer Lymphedema, Athletic Tape, Rehabilitation, Recovery of Function, Quality of Life and Clinical Laboratory Techniques''. Initially, 8,363 publications were obtained. After eliminating the duplicates and applying the inclusion and exclusion criteria, 17 articles remained. Results: Lymphotaping® may promote benefits in quality of life and in the volume and functionality of the arms affected by SCIM, although there are conflicting results that may be related to the methodological differences of the articles analyzed. Conclusion: Some studies showed that Linfotaping® was an interesting therapeutic alternative for SCIM. However, more solid evidence is needed, with the use of additional randomized clinical trials, larger samples, better defined populations, more descriptive methodologies and the use of other clinical and laboratory parameters to evaluate the effect of therapy.